Regulation of drug resistance to enrofloxacin in Pasteurella multocida strains from cattle by quorum-sensing acyl-homoserine lactone signaling molecules - Sun, Miao; Zhang, Zipeng; Han, Dongxu; Ge, Xinran; Wang, Yongqiang; Wang, Jianing; Li, Yue; Chen, Hengli; Xu, Boran; Ao, Kexin; Yang, Dahan; Liu, Kai; et al. (Frontiers in Microbiology, 2026)
Pasteurella multocida (Pm) is a significant cause of respiratory disease in beef cattle, with serious consequences for the cattle industry. The bacterial quorum-sensing (QS) system is used for communication and regulation of various processes, including bacterial growth, virulence, biofilm formation and antimicrobial resistance. This study investigated the effects of the C6 signaling molecule on Pm resistance to the antimicrobial enrofloxacin (ENR). Bacteria were divided into groups, with one group (Pm-E1) treated with sub-inhibitory concentrations of ENR, a second treated with sub-inhibitory concentrations of ENR + 200 μM C6 (Pm-E2), and a control group (Pm-YQ). Transcriptomic, proteomic, and metabolomic sequencing of the bacteria was then performed. The results showed that C6 increased the minimum inhibitory concentration of ENR against Pm from 0.25 μg/mL to 1 μg/mL. Differentially expressed genes (DEGs), proteins (DEPs), and metabolites (DEMs), with 798 DEGs, 249 DEPs, and 499 DEMs identified in the Pm-YQ vs. Pm-E1 group, while the Pm-E1 vs. Pm-E2 group contained 784 DEGs, 301 DEPs, and 397 DEMs. Further analysis of the DEGs, DEPs, and DEMs suggested potential mechanisms by which C6 might induce Pm resistance to ENR through regulating the SOS response, CpxAR two-component system, and the ABC transporter system. These findings not only provide insight into the QS-mediated drug resistance mechanisms in Pm, but also highlight the potential of targeting the QS system for the development of novel interventions to control pasteurellosis and counteract antimicrobial resistance.